The Influence of Local Own-Source Revenue, Human Development Index, and Labor Force Participation Level On GRDP Per Capita Moderate by the Depth of Poverty in City Districts of Papua Province in 2017-2021 - Putri, Alisa Noviani; Hariyanti, Dini; Adriana, Mona (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research aims to analyze the factors that influence GDP per capita in Papua Province. The analytical method used in this research is panel data regression, using data on Local Own-Source Revenue, Human Development Index, Labor Force Participation Level, and Gross Domestic Product Per Capita from 2017-2021 in districts/cities in Papua province, by adding the depth of poverty variable as a moderating variable. The results of panel data processing show that the best model is the Fixed Effect Model, with the regression results showing that the one that has a negative influence on GDP per capita is the HDI variable. Meanwhile, those that do not influence GDP per capita are the variables Local Own-Source Revenue, Human Development Index, Labor Force Participation Level, and Depth of Poverty. Many factors cause the variables used to have no influence, one of which is the minimal observation period so long-term effects were not identified, especially in this study. Another cause is the difficult geographical conditions in the form of mountains and difficult terrain to travel in these districts, hampering the mobility of people, goods, and services, as well as access to education and health services. The difficulty of this terrain also hinders efforts for equal distribution and economic development, so that access to economic development is only felt by urban areas, such as Jayapura City and its surroundings. This causes the Poverty Depth Index (P1) to be unable to moderate the variables of Local Own-Source Revenue (PAD), Human Development Index (HDI), and Labor Force Participation Level (TPAK) on GDP per capita. It is recommended for future researchers to use all provinces in Papua and add other variables.